2018
DOI: 10.1080/00131911.2018.1471664
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the explanations for Asian American scholastic success: a meta-analytic and critical review

Abstract: A few popular explanations attempt to argue for a weaker relationship between socioeconomic status (SES), parental involvement (PI), and achievement among Asian Americans compared to their white counterparts: Asian American students' Confucian culture, strong motivation for upward mobility as immigrants, unique forms of parental involvement different from European Americans, and ethnic social capital. However, there has not been a single synthesis up to date empirically testing whether the effect size for SES … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 77 publications
(160 reference statements)
0
6
0
Order By: Relevance
“…Although some meta-analyses also examined partial correlations or used multiple regression (i.e., controlling for IQ or high school GPA), there were no tests of the pathways that may explain why SES is related to performance on measures of cognitive ability and achievement. One meta-analysis provided a qualitative review of cultural factors proposed to link SES to academic achievement among Asian Americans (immigrant optimism and Confucian culture), but found weak support (Kim et al., 2018). Another meta-analysis concluded that the effect between SES and college grades is mediated by admissions test scores because the average effect between SES and college grades decreased substantially when controlling for test scores (Sackett et al., 2009).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although some meta-analyses also examined partial correlations or used multiple regression (i.e., controlling for IQ or high school GPA), there were no tests of the pathways that may explain why SES is related to performance on measures of cognitive ability and achievement. One meta-analysis provided a qualitative review of cultural factors proposed to link SES to academic achievement among Asian Americans (immigrant optimism and Confucian culture), but found weak support (Kim et al., 2018). Another meta-analysis concluded that the effect between SES and college grades is mediated by admissions test scores because the average effect between SES and college grades decreased substantially when controlling for test scores (Sackett et al., 2009).…”
Section: Resultsmentioning
confidence: 99%
“…The relation between SES and academic achievement was often larger for samples with more White participants compared to non-White participants (e.g., Harwell et al., 2017). One meta-analysis focused only on Asian Americans even found a null effect size (Kim et al., 2018). In contrast, Lawson et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Asian American groups do not distinguish between various subgroups: The “Asian American” classification includes not only Korean Americans and Chinese Americans but also Pacific Islander, Native Hawaiian, Samoan American, Chamorro, Cambodian American, Hmong American, Vietnamese American, Indian American, and Filipino American groups. However, they are described as a homogeneous group sharing a Confucian tradition leading to their high achievement, which has been a point of criticism (Kim, Cho, & Song, 2018; Lee & Zhou, 2014). Despite these issues, one commonality we can tease out between our East Asian sample and the Asian Americans represented here are their locale of origin and “high-achieving” characteristic: The East Asian countries represented in our sample have acquired the reputation for scoring well on PISA tests, whereas Asian Americans are seen to be successful in school, with various explanations and descriptions of their academic success.…”
Section: Resultsmentioning
confidence: 99%
“…Parental involvement in children's education is widely acknowledged as a crucial factor influencing youth development. In particular, parental involvement has been found to coincide with children's academic achievement (Castro et al, 2015;Fan & Chen, 2001;Jeynes, 2003Jeynes, , 2012Jeynes, , 2015Jeynes, , 2016Jeynes, , 2017Kim, 2020;Kim et al, 2019;Ma et al, 2016). After the transition from primary to secondary school, the importance of academic achievement continuously increases (e.g., Barber & Olsen, 2004).…”
Section: Introductionmentioning
confidence: 99%